Pelos pequenos trabalhadores do Novo Mundo: OIT e trabalho infantojuvenil nas Américas (1936-1939) - Santos Júnior, José Pacheco dos (2017)
Created in 1919, the International Labour Organization took on a bold task: to standardize the world of work and to consolidate the ideal of social justice as a way of consolidate world peace. Choosing this agency as an object of study, the article aims to analyze the formulation and purposes that defined the resolutions on the work of children and young people, discussed and approved in the first two American Labour Conferences, held in Chile (1936) and in Cuba (1939). Under comparative analysis, the reflection concludes that the resolutions coming from such forums were not only to regulate but also to conform ideal models of childhood and youth